The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/aem.01675-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Filamentous Phage SW1 in Regulating the Lateral Flagella of Shewanella piezotolerans Strain WP3 at Low Temperatures

Abstract: b Low-temperature ecosystems represent the largest biosphere on Earth, and yet our understanding of the roles of bacteriophages in these systems is limited. Here, the influence of the cold-active filamentous phage SW1 on the phenotype and gene transcription of its host, Shewanella piezotolerans WP3 (WP3), was investigated by construction of a phage-free strain (WP3⌬SW1), which was compared with the wild-type strain. The expression of 49 genes, including 16 lateral flagellar genes, was found to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 48 publications
4
34
0
3
Order By: Relevance
“…From this respect, the activity of deep‐sea sediment phage SW1 and its influence on bacterial host are worth to be investigated although some marine or terrestrial isolated phages have been studied. Our previous study has shown that the bathypelagic filamentous phage SW1 have a significant influence on transcription of 49 genes (including 16 lateral flagellar genes) and swarming motility of WP3 at 4°C (Jian et al ., ). In this study, the activity of SW1 was shown to significantly affect the growth and transcriptome of its deep‐sea bacterial host.…”
Section: Introductionmentioning
confidence: 97%
“…From this respect, the activity of deep‐sea sediment phage SW1 and its influence on bacterial host are worth to be investigated although some marine or terrestrial isolated phages have been studied. Our previous study has shown that the bathypelagic filamentous phage SW1 have a significant influence on transcription of 49 genes (including 16 lateral flagellar genes) and swarming motility of WP3 at 4°C (Jian et al ., ). In this study, the activity of SW1 was shown to significantly affect the growth and transcriptome of its deep‐sea bacterial host.…”
Section: Introductionmentioning
confidence: 97%
“…To date, a number of Shewanella phages (both lytic and temperate) have been described from marine and freshwater environments [17,18,19,20,21], and in Shewanella oneidensis , prophages have also been implicated as vital for biofilm formation through excision-mediated lysis [21]. Stably integrated prophage-like elements are common within the genomes of most marine bacterial species [22], and prophages are also thought to be important among bacteria that colonize the gut mucosa of animals [23], often forming biofilms [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide a broad knowledge base for constructing the WP3 GEM. Furthermore, WP3 has established protocols for genetic manipulations (3740). The experimental accessibility of this organism would enable the verification of modeling outcomes and support future research on molecular adaptations through combined GEM simulation and experimental verification.…”
Section: Introductionmentioning
confidence: 99%